Comparative Influence of Service Quality on Customer Satisfaction Level Between Bank BSI and Bank ACEH - mutia, faliza; Rahmawati, Rahmawati; khairina, khalish (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study is entitled "Comparative Study of the Influence of Service Quality on Customer Satisfaction Level between BSI Bank and Aceh Bank (Case Study of FEBI IAIN Lhokseumawe Students)" The background of this study is based on the rapid development of Islamic banking in Indonesia, especially Bank Syariah Indonesia (BSI) as a national bank and Bank Aceh Syariah (BAS) as a regional bank. Although both are Sharia-based, there are differences in students' perceptions of service quality and the level of satisfaction provided by each bank. This study aims to determine : (1) The influence of service quality on customer satisfaction of Bank BSI, (2) The influence of service quality on customer satisfaction of Bank Aceh, and (3) Comparison of the influence of service quality on customer satisfaction between Bank BSI and Bank Aceh. The method used is a comparative quantitative approach with data collection techniques through distributing questionnaires to 94 FEBI IAIN Lhokseumawe students who are customers of both Banks . Data analysis techniques include validity test, reliability test , classical assumption test , simple linear regression, and independent sample t- test . The results of the study indicates that service quality at Bank BSI has a contribution to customer satisfaction of 26.1% (R² = 0.261), but is not statistically significant (p = 0.416 > 0.05). Meanwhile , the effect of service quality on customer satisfaction at Bank Aceh is only 8.9% (R² = 0.089).